The use of nasal markers for monitoring mallard populations - Fabião, António (2001)
We discuss the advantages and limitations of alphanumeric-coded nasal markers used for monitoring resident mallard populations. We tested two designs of nasal saddles, various colours, PVC tape of 2 thicknesses and ribber tape. The rctangular nasal saddle could disturb birds during feeding, so we changed it to a more anatomical design. The use of alphanumeric coded nasal markers was an efficient method for marking mallards in small wetlands with good visibility and for relatively short periods.